Nationally Marked Stereotypes in Phraseological Units of the Polish and Ukrainian Languages - Дем’яненко, Наталія Борисівна (Київського національного університету імені Тараса Шевченка, 2025)
The article focuses on the analysis of stereotypes reflected in Polish and Ukrainian ethnophraseology, which constitute a significant part of the national and cultural worldview. Particular attention is devoted to the comparison of phraseological units with ethnonymic components that convey traditional perceptions, evaluations, and prejudices regarding both “own” and “foreign” ethnic groups. The article examines phraseological expressions with the components Jew (Żyd), German, Gypsy, Russian (Muscovite), Hungarian, Romanian, Bulgarian, Turk, and Tatar, which function in the Polish and Ukrainian languages and demonstrate both common and distinctive features in the formation of ethnocultural images. The methodological basis of the study is a combination of cognitive and cultural approaches, which makes it possible to interpret phraseologisms not only as linguistic clichés but also as value markers that accumulate social experience and reflect historical contacts, conflicts, and intercultural relations. The research material consists of data from Polish and Ukrainian lexicographic sources, supplemented by examples from literary language and online sources. The aim of the article is to identify, analyze, and compare phraseological units of Polish and Ukrainian that contain ethnonyms or other ethnoconnotative components, in order to reconstruct linguistic stereotypes about other nations and peoples. The analysis has shown that Polish and Ukrainian ethnophraseology records a number of similar stereotypes formed on the basis of shared history, geographical proximity, and contacts with neighboring peoples. The study identified a set of phraseological units with ethnic markers in Polish and Ukrainian, carried out their semantic analysis, and classified them according to types of ethnic stereotypes (positive, negative, neutral). Furthermore, both common and divergent features of stereotypical images preserved in the phraseology of the two languages were established. The conclusions emphasize that phraseology is an important source for studying ethnic stereotypes, as it reflects collective representations that preserve the cultural memory of a people. The comparison of Polish and Ukrainian material makes it possible to trace both universal patterns of stereotyping and the specificity of the national worldview.

Стаття зосереджена на аналізі стереотипів, відображених у польській та українській етнофразеології, які становлять вагому частину національно-культурної картини світу. Основну увагу приділено порівнянню фразеологічних одиниць з етнонімним компонентом, що відображають традиційні уявлення, оцінки й упередження стосовно «своїх» та «чужих» етносів. У статті розглядаються фразеологізми з компонентами єврей (жид), німець, циган, росіянин (москаль), угорець, румун, болгарин, турок, татарин, які функціонують у польській та українській мовах і демонструють як спільні, так і відмінні особливості формування етнокультурних образів. Методологічною основою дослідження є поєднання когнітивного та культурологічного підходів, що дозволяє інтерпретувати фразеологізми не лише як мовні кліше, а й як ціннісні маркери, що акумулюють суспільний досвід і відображають історичні контакти, конфлікти та міжкультурні взаємини. Матеріалом дослідження слугували дані польських та українських лексикографічних джерел, принагідно використовувались дані мови художньої літератури та інтернет джерел. Метою статті було виявлення, аналіз і зіставлення фразеологізмів польської та української мов, що містять етноніми або інші етноконнотативні компоненти, для реконструкції мовних стереотипів про інші нації та народи. Проведений аналіз показав, що польська та українська етнофразеологія фіксують низку подібних стереотипів, сформованих на ґрунті спільної істо- рії, географічної близькості та контактів із сусідніми народами. У ході дослі- дження було визначено коло фразеологічних одиниць з етнічними маркерами у польській та українській мовах, здійснено їх семантичний аналіз; усі фразеологізми було розкласифіковані за типами етнічних стереотипів (позитивні, негативні, нейтральні). Крім того, було встановлено спільні й відмінні риси у стереотипних образах, закріплених у фразеології обох мов. У висновках підкреслено, що фразеологія є важливим джерелом дослідження етнічних стереотипів, адже вона відбиває колективні уявлення, що зберігають культурну пам’ять народу. Порівняння польського та українського матеріалу дає можливість простежити як універсальні закономірності стереотипізації, так і специфіку національного світогляду.
Національно марковані стереотипи у фразеологічних одиницях польської та української мов
Keywords: phraseological unit; ethnophraseology; stereotype; ethnonym; Polish language; Ukrainian language; national and cultural worldview; фразеологізм; етнофразеологія; стереотип; етнонім; польська мова; українська мова; національно-культурна картина світу